Acute peri‐operative neurocognitive disorders: a narrative review. (10th January 2022) - Evered, L.; Atkins, K.; Silbert, B.; Scott, D. A.
Summary: Peri‐operative neurocognitive disorders are the most common complication experienced by older individuals undergoing anaesthesia and surgery. Peri‐operative neurocognitive disorders, particularly postoperative delirium, result in long‐term poor outcomes including: death; dementia; loss of independence; and poor cognitive and functional outcomes. Recent changes to the nomenclature of these disorders aims to align peri‐operative neurocognitive disorders with cognitive disorders in the community, with consistent definitions and clinical diagnosis. Possible mechanisms include: undiagnosed neurodegenerative disease; inflammation and resulting neuroinflammation; neuronal damage; and comorbid systemic disease. Pre‐operative frailty represents a significant risk for poor postoperative outcomes; it is associated with an increase in the incidence of cognitive decline at 3 and 12 months postoperatively. In addition to cognitive decline, frailty is associated with poor functional outcomes following elective non‐cardiac surgery. It was recently shown that 29% of frail patients died or experienced institutionalisation or new disability within 90 days of major elective surgery. Identification of vulnerable patients before undergoing surgery and anaesthesia is the key to preventing peri‐operative neurocognitive disorders. Current approaches include: pre‐operative delirium and cognitive screening; blood biomarker analysis; intra‐operative management that may reduce the incidence of postoperative delirium such as lighter anaesthesia using processed electroencephalography devices; and introduction of guidelines which may reduce or prevent delirium and postoperative neurocognitive disorders. This review will address these issues and advocate for an approach to care for older peri‐operative patients which starts in the community and continues throughout the pre‐operative, intra‐operative, postoperative and post‐discharge phases of care management, involving multidisciplinary medical teams, as well as family and caregivers wherever possible.